In-depth Analysis on Strengthening Sanctions for Fisheries Violations in Indonesia: Challenges, Obstacles, and Reform - Shafira, Maya; Akib, Muhammad; Sumarja, FX; Fardiansyah, Ahmad Irzal (UI Scholars Hub, 2025)
Illegal, Unreported, and Unregulated (IUU) Fishing remains a significant challenge for Indonesia, posing threats to its marine resources, economic stability, and national sovereignty. This study examines the enforcement of sanctions against fisheries violations in Indonesia from an international legal perspective. It explores how Indonesia aligns its regulatory framework with global legal instruments, such as the United Nations Convention on the Law of the Sea (UNCLOS), the Port State Measures Agreement (PSMA), and regional agreements within ASEAN. The research identifies key challenges, including legal inconsistencies, enforcement limitations, and jurisdictional complexities, which hinder the effective prosecution of fisheries crimes. It also analyzes obstacles in implementing stricter sanctions, particularly in cases involving foreign fishing vessels operating illegally in Indonesian waters. The study also assesses Indonesia’s current legal reforms and proposes policy recommendations to enhance compliance with international norms. Strengthening cooperation with neighboring countries, improving monitoring and surveillance systems, and reforming legal mechanisms are crucial steps toward ensuring more effective sanctions. By integrating international legal standards into domestic policies, Indonesia can enhance its ability to combat fisheries violations while fostering sustainable marine resource management.